2013
DOI: 10.1111/j.1464-410x.2012.11648.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of family history of prostate cancer and genetic risk single nucleotide polymorphism (SNP) profiles in an active surveillance cohort

Abstract: Objectives To explore the potential prognostic role of family history (FH) of prostate cancer and prostate cancer risk single nucleotide polymorphisms (SNPs) in patients undergoing active surveillance (AS) for prostate cancer. This is the first study to date, which has investigated the potential prognostic role of SNP profiles in an AS cohort Patients and methods FH data were collected from patients in the Royal Marsden Hospital AS study. In all, 39 prostate cancer-risk SNPs identified from publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
0
29
1
Order By: Relevance
“…Larger studies are required to confirm the differences observed. Little is known about the effect of FH on PrCa progression and the benefits of early diagnosis in this group [14]. All but one man diagnosed with low-risk PrCa accepted active surveillance, highlighting the growing understanding of the natural history of PrCa and the increasing acceptance of a structured monitoring strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies are required to confirm the differences observed. Little is known about the effect of FH on PrCa progression and the benefits of early diagnosis in this group [14]. All but one man diagnosed with low-risk PrCa accepted active surveillance, highlighting the growing understanding of the natural history of PrCa and the increasing acceptance of a structured monitoring strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search identified 30 original articles that were included for review: 14 on magnetic resonance imaging (MRI) [8][9][10][11][12][13][14][15][16][17][18][19][20][21], 5 on serum markers [22][23][24][25][26], 5 on urinary markers [27][28][29][30][31], 4 on histopathology markers [32][33][34][35], and 2 on germline genetic markers [36,37]. Figure 1 presents the search strategy and study selection flowchart.…”
Section: Search Resultsmentioning
confidence: 99%
“…Goh et al studied the predictive value of 29 cancer risk-associated single nucleotide polymorphisms and family history in AS patients (n = 471) [36]. This retrospective study found no association with the intermediate end points, adverse repeat biopsy findings, and time to treatment.…”
Section: Germline Genetic Markersmentioning
confidence: 99%
“…On the contrary, Iremashvili and colleagues (9) aimed to identify clinical and demographic characteristics associated with an increased probability of progression and found no significant association for age, family history or baseline PSA. Several other studies also showed no relationship between family history with PSA growth (38), high grade disease (18), Gleason 4 (33), or time to treatment (39). …”
Section: Evidence Synthesismentioning
confidence: 96%